The Influence of Tl4Bi2S5 Precipitates on the Crystalline TlBiS2 Properties - Özer, Mehmet; Kalkan, N; Kyritsi, KG; Paraskevopoulos, KM; Anagnostopoulos, AN; Stergioudis, G; Polychroniadis, EK (WILEY-V C H VERLAG GMBH, PO BOX 10 11 61, D-69451 WEINHEIM, GERMANY, 2002)
Crystalline TlBiS2 having homogeneously distributed Tl4Bi2S5 precipitates was grown by the vertical Bridgman technique in a two-step procedure. X-rays and Transmission Electron Microscopy (TEM) studies were used to identify the as-grown material whereas a Scanning Electron Microscopy (SEM) examination revealed its layered structure. The electrical conductivity a was measured both along (sigma(parallel to)) and across (sigma(perpendicular to)) its layers. IR reflectivity measurements were also performed and the plasma minimum was determined. Both electrical and optical characterization show properties similar to those of TlBiS2 but a reduced N/m* ratio and an irregular voltage oscillation in the I-U characteristics were deduced. Combining the results from these investigations a possible explanation was proposed.
Keywords: optical properties; single crystals; semiconductor; density; Growth; states; optik özellikler; tek kristaller; yarıiletken; yoğunluk; büyüme; derece